2018
DOI: 10.3357/amhp.4975.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ice Slurry Ingestion and Physiological Strain During Exercise in Non-Compensable Heat Stress

Abstract: A large quantity of ice slurry ingested under non-compensable heat stress conditions mitigated physiological strain during exercise by blunting the rise in heart rate and rectal temperature.Ng J, Wingo JE, Bishop PA, Casey JC, Aldrich EK. Ice slurry ingestion and physiological strain during exercise in non-compensable heat stress. Aerosp Med Hum Perform. 2018; 89(5):434-441.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“… 24 It was also reported that ice slurry ingestion during exercise wearing fireproof clothing suppressed the elevation in T re . 33 In our experiments, the elevations of and T int were significantly suppressed for approximately 30 minutes after the start of exercise in the ICE condition. It has been demonstrated that and T int reflect dynamic changes in contrast with T re , which might have affected the results.…”
Section: Discussionsupporting
confidence: 48%
“… 24 It was also reported that ice slurry ingestion during exercise wearing fireproof clothing suppressed the elevation in T re . 33 In our experiments, the elevations of and T int were significantly suppressed for approximately 30 minutes after the start of exercise in the ICE condition. It has been demonstrated that and T int reflect dynamic changes in contrast with T re , which might have affected the results.…”
Section: Discussionsupporting
confidence: 48%
“…Our search identified 558 abstracts. Initially, 101 reports seemed possibly relevant, but after a thorough full-text review, only 47 studies were included ( Lee and Shirreffs, 2007 ; Lee et al, 2008 ; Lee et al, 2008 ; Burdon et al, 2010 ; Ihsan et al, 2010 ; Stanley et al, 2010 ; Byrne et al, 2011 ; Siegel et al, 2011 ; Bain et al, 2012 ; Siegel et al, 2012 ; Burdon et al, 2013 ; Hue et al, 2013 ; Brade et al, 2014 ; Morris et al, 2014 ; Burdon et al, 2015 ; Hue et al, 2015 ; James et al, 2015 ; Lamarche et al, 2015 ; Pryor et al, 2015 ; Schulze et al, 2015 ; Zimmermann and Landers, 2015 ; Hailes et al, 2016 ; Morris et al, 2016 ; Stevens et al, 2016 ; Tay et al, 2016 ; Flood et al, 2017 ; Gerrett et al, 2017 ; Takeshima et al, 2017 ; Zimmermann et al, 2017 ; Zimmermann et al, 2017 ; Jeffries et al, 2018 ; Ng et al, 2018 ; Snipe and Costa, 2018 ; Watkins et al, 2018 ; Aldous et al, 2019 ; Gibson et al, 2019 ; Ng et al, 2019 ; Thomas et al, 2019 ; Iwata et al, 2020 ; Naito et al, 2020 ; Nakamura et al, 2020 ; Onitsuka et al, 2020 ; Saldaris et al, 2020 ; Alhadad et al, 2021 ; Gavel et al, 2021 ; Parton et al, 2021 ; Tabuchi et al, 2021 ). The kappa value of 0.76 for the agreement between the two researchers assessing the eligibility of records was considered to reflect a “substantial” agreement ( Orwin et al, 1994 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested the possibility that ice slurry ingestion provided a sufficient heat sink to decrease heat storage and thereby reduce cardiovascular strain [ 32 ]. The other study also reported that ice slurry ingestion during walking at 4.0 km·h −1 on a 12% incline wearing firefighter-protective clothing decreased HR by approximately 10 bpm at 5 min of the commencement of walking compared to cold fluid [ 33 ]. However, this is only speculative, and further research is warranted to investigate the mechanism of the decrease in HR following ice slurry ingestion.…”
Section: Discussionmentioning
confidence: 99%